Learning motivation and environmental support: how first-generation college students achieve success? - Li, Xiaojing; Liu, Weitong; Hu, Ke (Frontiers in Psychology, 2023)
With the continuous expansion of higher education across the worldworldwide, the academic performance of the first-generation college students has become an important essential topic in the scope of international educational research. This study examines the impact of learning motivation (i.e., intrinsic and extrinsic motivationinternal and external motivation) and environmental support (i.e., instructional, relational, and campus support) on the academic development outcomes of firstgeneration college students, based on the Cultural Mismatch Theory and Self-Determination Theory from both individual and environmental perspectives. A total of 87418 data were collected from the China College Student Survey (CCSS) 20202020 "Chinese College Students Learning and Development Tracking Study", among which 58,864 were first-generation college students. Data analysis revealed in terms ofthat intrinsicnternal learning motivation, relational support, campus support, and academic performance of first-generation college students are significantly lower than those of non-first-generation students. However, this study found no significant differences were found concerning external learning motivation and teaching support. The subsequence regression analysis showed, both that both learning motivation and environmental supported positively predicted academic achievementslearning outcomes, with intrinsicnternal learning motivation having the strongest most substantial influence. Moreover, learning motivation and environmental support interact each other in jointly promoting the students' student's academic success. This study sheds light on the influencing factors and mechanisms of the academic development for of the firstgeneration college students.